The sinister sweetness of Splendid Academy - Loftin, Nikki (Razorbill, 2012)
In this twist on "Hansel and Gretel," two middle schoolers find themselves in a new charter school filled with a mysterious abundance of food at mealtimes and sinister teachers up to no good.